Amphipathic chitosans improve the physicochemical properties of siRNA-chitosan nanoparticles at physiological conditions. (15th July 2019) - Martins, Grazieli Olinda; Segalla Petrônio, Maicon; Furuyama Lima, Aline Margarete; Martinez Junior, André Miguel; de Oliveira Tiera, Vera Aparecida; de Freitas Calmon, Marília; Leite Vilamaior, Patricia Simone; Han, Sang Won; Tiera, Marcio José
Graphical abstract: Highlights: Chitosan derivatives were synthesized and characterized. Amphipathic character is tuned by degree of acetylation and tertiary amino groups. Charge density and hydrophobic forces improves the coacervation process of siRNA into nanoparticles. Chitosan-siRNA nanoparticles with improved colloidal stability at physiological conditions are obtained. Abstract: Chitosan has received a lot of attention as a carrier for small interfering RNA (siRNA), due to its capacity for complexation and intracellular release of these molecules. However, one of its limitations is its insolubility at neutral pH and the tendency towards aggregation of its nanoparticles in isotonic ionic strength. In this study, a series of amphipathic chitosans were synthesized by varying the degree of acetylation (DA) from ˜2 to ˜30 mol% and the degree of substitution (DS) from 5 to 25%. by tertiary amino groups (DEAE) The results showed that the adjustment of these parameters decreases the interparticle interactions mediated by hydrogen bonding to obtain nanoparticles with improved colloidal stability. siRNA-containing nanoparticles of 100 to 150 nm with low polydispersities (0.15–0.2) and slightly positive zeta potentials (˜+ 5 mV) were resistant to aggregation at pH 7.4 and ionic strength of 150 mM. This resistance to aggregation is provided by changes on the nanoparticle surface and highlights the importance of more organized self-assembly in providing colloidal stability at physiological conditions. Additionally, the PEGylation of the most promising vectors conferred favorable physicochemical properties to nanoparticles. The chitosans and their nanoparticles exhibited low toxicity and an efficient cell uptake, as probed by confocal microscopy of rhodamine labeled vectors. The results provide a new approach to overcome the limited stability of chitosan nanoparticles at physiological conditions and show the potential of these amphipathic chitosans as siRNA carriers.